2017
DOI: 10.13075/ijomeh.1896.00724
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders and perception of working conditions: A survey of Brazilian dentists in São Paulo

Abstract: Objectives: To investigate the prevalence of work-related musculoskeletal disorders amongst dentists who work in public clinics in São Paulo, Brazil, to investigate their awareness of the presence of risk factors in the workplace, disability due to pain, and the influence of pain on this awareness and disability. Material and Methods: A cross-sectional study was conducted among 204 dentists who work in public health clinics in the northwest of São Paulo, Brazil. The data was collected through interviews, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
5
18
0
9
Order By: Relevance
“…According to findings of this study, 86.9% of dentists had problems in at least one of their limbs before the educational intervention. A study conducted by Ísper Garbin et al (2017) on 204 dentists [21], a study carried out by Nokhostin and Zafarmand (2016) on 600 Iranian dentists [11], a study of Munshi et al (2016) on 420 Indian dentists [22], and a study conducted by Abi Aad (2016) on 218 Lebanese dentists [23] showed prevalence of musculoskeletal disorders equal to 81.4%, 67.5%, 90.7%, and 92.7%, respectively. According to the mentioned studie that confirmed the results of each other, there is a considerable prevalence of musculoskeletal disorders among dentists indicating lack of awareness of correct ergonomic principles and lack of stretching exercises between patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to findings of this study, 86.9% of dentists had problems in at least one of their limbs before the educational intervention. A study conducted by Ísper Garbin et al (2017) on 204 dentists [21], a study carried out by Nokhostin and Zafarmand (2016) on 600 Iranian dentists [11], a study of Munshi et al (2016) on 420 Indian dentists [22], and a study conducted by Abi Aad (2016) on 218 Lebanese dentists [23] showed prevalence of musculoskeletal disorders equal to 81.4%, 67.5%, 90.7%, and 92.7%, respectively. According to the mentioned studie that confirmed the results of each other, there is a considerable prevalence of musculoskeletal disorders among dentists indicating lack of awareness of correct ergonomic principles and lack of stretching exercises between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in other research. Ísper Garbin et al (2017) carried out a study on 204 dentists and reported more musculoskeletal disorders in neck, shoulders, and lower back [21]. Munshi et al (2016) carried out a study on 420 dentists and reported neck (73.8%), lower back (70%), wrist and hand (64%), and shoulders (62.4%) as the most involved parts of body [22].…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, several studies investigated the prevalence of WMSD or CTS among practicing dentists in Australia,10 Brazil,11 China,12 Czech Republic,13 India,9 Iran,14 Pakistan,8 Spain,7 Taiwan,15 and Turkey 16. Studies investigating MSD in Saudi Arabia focused either on dental students as the population of interest,17,18 or in specific regions of Saudi Arabia as Riyadh,19,20 and Hail 21.…”
Section: Introductionmentioning
confidence: 99%
“…Work-related musculoskeletal (MS) disorders are considered one of the most frequent occupational diseases among dental workers (Hayes, Cockrell, & Smith, 2009;Melhorn, 2000). Prior studies reported the frequency of MS disorders among dental workers, ranging from 63% to 93% (Isper Garbin, Barreto Soares, Moreira Arcieri, Saliba Garbin, & Siqueira, 2017;Nasl Saraji, Hosseini, Shahtaheri, Golbabaei, & Ghasemkhani, 2005;Rabei, Shakiba, Shahreza, & Talebzadeh, 2011). MS disorders are defined as inflammatory and degenerative diseases or disorders of muscles, ligaments, tendons, nerves, blood vessels, bones, and joints that can result in pain (Hayes et al, 2009;Melhorn, 2000).…”
Section: Introductionmentioning
confidence: 99%